2003
DOI: 10.1515/bc.2003.100
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage Site Specificity of Cathepsin K toward Cartilage Proteoglycans and Protease Complex Formation

Abstract: Cathepsin K is a potent extracellular matrix-degrading protease that requires interactions with soluble glycosaminolycans for its collagenolytic activity in bone and cartilage. The major sources of glycosaminoglycans in cartilage are aggrecan aggregates. Therefore, we investigated whether cathepsin K activity is capable to hydrolyze aggrecan into fragments allowing the formation of glycosaminoglycan-cathepsin K complexes and determined the cleavage site specificity of cathepsin K toward the cartilage-resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 32 publications
1
66
0
Order By: Relevance
“…However, only a subset of GAGs allowed the generation of collagenolytically active complexes. Interestingly, these were GAGs that are predominantly expressed in bone and cartilage (chondroitin sulfates and keratan sulfates), the sites of the probably main biological activity of cathepsin K. These GAGs are easily liberated by cathepsin activities from aggregan aggregates or cartilage and can subsequently form complexes with cathepsin K (39). Other GAGs such as dermatan sulfate, heparan sulfate, and heparin are also able to form stable complexes but do not support any collagenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a subset of GAGs allowed the generation of collagenolytically active complexes. Interestingly, these were GAGs that are predominantly expressed in bone and cartilage (chondroitin sulfates and keratan sulfates), the sites of the probably main biological activity of cathepsin K. These GAGs are easily liberated by cathepsin activities from aggregan aggregates or cartilage and can subsequently form complexes with cathepsin K (39). Other GAGs such as dermatan sulfate, heparan sulfate, and heparin are also able to form stable complexes but do not support any collagenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the P1 position, the substrate preference is similar in cathepsin L and K with a preference for amino acids with a hydrophilic side chain such as Arg, Lys, Gln, or Met (31,67,68), although amino acids with short side chains such as Gly or Ser can also be allowed (69,70 Both cathepsin K and L are expressed in osteoclasts (71), although cathepsin K is more abundant than cathepsin L at the mRNA (72,73) and activity (52) levels. Our RT-PCR and Western blot analysis on bone extracts and immunohistochemistry on bone tissue sections clearly indicated a higher expression of cathepsin K versus L in trabecular osteoclasts and, moreover, indicated that the majority of cathepsin K protein was processed to the active form and co-localized with TRAP in osteoclasts, whereas the majority of cathepsin L was present as the inactive precursor form and did not co-localize to a significant extent with TRAP in osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Besides collagens, cathepsin K cleaves a variety of other bone-and cartilage resident proteins such as osteonectin, aggrecan, and IGF-1 [22,23].…”
Section: Introductionmentioning
confidence: 99%